(untitled) (Research, Society and Development, 2025)
The objective of the present study is to demonstrate how this partnership is not just a measure for cost reduction, but a lever for global competitiveness, enabling companies to navigate with greater security, efficiency, and flexibility in an increasingly volatile and demanding business environment. Globalization and the growing complexity of supply chains have made logistics a strategic pillar for corporate competitiveness. The import process, in particular, requires complex management that ranges from transportation and warehousing to customs clearance and distribution. Outsourcing these activities to a Third-Party Logistics (3PL) provider is a solution to optimize operations. The main advantage of logistics outsourcing is that it allows companies to focus on their core competencies. By transferring logistics functions to specialists, organizations can reduce operational costs, turn fixed expenses into variable ones, and gain access to advanced technologies and qualified professionals. Outsourcing also increases process efficiency, productivity, and flexibility.